ANALISIS MINAT BELAJAR SERTA DAMPAKNYA TERHADAP KESULITAN BELAJAR MATEMATIKA DI KELAS V SD - Septian Alya Hustria; Tya Noviyanti (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to analyze students’ learning interest and its impact on mathematics learning difficulties in fifth-grade elementary school. Mathematics plays a crucial role in developing logical, critical, and systematic thinking skills; however, many students perceive it as a difficult and uninteresting subject. This perception often leads to low learning interest, which contributes to learning difficulties. This research employs a qualitative approach using a literature review method by examining various relevant journals and scientific articles. Data were collected through documentation techniques and analyzed descriptively by identifying patterns and relationships between variables. The findings reveal that learning interest has a significant influence on students’ mathematics learning difficulties. Students with high learning interest tend to be more active, engaged, and capable of understanding mathematical concepts, while those with low interest often experience difficulties in comprehension and problem-solving. In addition, both internal factors (such as motivation and attitude) and external factors (such as family environment and teaching methods) also contribute to these difficulties. Therefore, increasing students’ learning interest is essential to reduce mathematics learning difficulties. Teachers are encouraged to implement innovative and engaging teaching strategies, while parents should provide supportive learning environments. In conclusion, learning interest is a key factor in improving students’ understanding and minimizing difficulties in mathematics learning.